Comparison of gene transfection and cytotoxicity mechanisms of linear poly(amidoamine) and branched poly(ethyleneimine) polyplexes - Almulathanon, Ammar A.Y.; Ranucci, Elisabetta; Ferruti, Paolo; Garnett, Martin C.; Bosquillon, Cynthia (Springer, 2018)
Purpose: This study aimed to further explore the mechanisms behind the ability of certain linear polyamidoamines (PAAs) to transfect cells with minimal cytotoxicity. Methods: The transfection efficiency of DNA complexed with a PAA of a molecular weight over 10 kDa or 25 kDa branched polyethyleneimine (BPEI) was compared in A549 cells using a luciferase reporter gene assay. The impact of endo/lysosomal escape on transgene expression was investigated by transfecting cells in presence of bafilomycin A1 or chloroquine. Cytotoxicity caused by the vectors was evaluated by measuring cell metabolic activity, lactate dehydrogenase release, formation of reactive oxygen species and changes in mitochondrial membrane potential. Results: The luciferase activity was 3-fold lower after transfection with PAA polyplexes than with BPEI complexes at the optimal polymer to nucleotide ratio (RU:Nt). However, in contrast to BPEI vectors, PAA polyplexes caused negligible cytotoxic effects. The transfection efficiency of PAA polyplexes was significantly reduced in presence of bafilomycin A1 while chloroquine enhanced or decreased transgene expression depending on the RU:Nt. Conclusions: PAA polyplexes displayed a pH-dependent endo/lysosomal escape which was not associated with cytotoxic events, unlike observed with BPEI polyplexes. This is likely due to their greater interactions with biological membranes at acidic than neutral pH.